The Role of 5-Hydroxytryptamine in the Pathophysiology of Migraine and its Relevance to the Design of Novel Treatments - M. Villalón, Carlos; Maassen VanDenBrink, Antoinette (Mini Reviews in Medicinal Chemistry, 2017)
Background: Migraine is a highly prevalent neurovascular disorder. Objective: Of the many factors that have been implicated over the years, 5-hydroxytryptamine (5-HT;serotonin) has long been involved in the pathophysiology of migraine. Certainly, some lines of evidence suggest: (i) a 5-HT depletion from blood platelets resulting in cranial extracerebral vasodilatation; and (ii) the effectiveness of an intravenous (i.v.) infusion of 5-HT to abort migraine in some patients. More direct evidence comes from some drugs that influence 5-HT release and/or interact (as agonists or antagonists) with 5-HT receptors to treat this disorder. Indeed, the development of sumatriptan and second generation triptans in the 1990’s led to discover that these drugs produce selective cranial extracerebral vasoconstriction (via 5-HT1B receptors) and inhibition of the trigeminovascular system responses implicated in migraine (via 5-HT1D/5-HT1F receptors). Although the triptans represent the current mainstay of acute antimigraine treatment, a number of patients do not respond well to the triptans and are contraindicated in patients with cardiovascular pathologies. Conclusion: This mini-review outlines further developments in the design of novel (non-vasoconstrictor) antimigraine treatments acting via 5-HT receptors, including selective agonists at 5-HT1D and 5-HT1F receptors, agonists at 5-HT1B/1D receptors combined with other properties as well as antagonists at 5-HT2B/2C, 5-HT3 and 5-HT7 receptors. It also touches upon the recent development of antagonists and antibodies at calcitonin gene-related peptide (CGRP) and its receptors, which produce a direct blockade of the CGRPergic vasodilator mechanisms involved in migraine. These alternative pharmacological approaches will hopefully lead to less side-effects.s.
Keywords: Antimigraine drugs